Evaluating the Characteristics of Local Nutmeg Powder and Oil in Relation to Industrial Standard of Nutmeg - Rifda Naufalin; Condro Wibowo; Rumpoko Wicaksono; Nuke Faradhila; Ardiansyah Ardiansyah; Suliyanto Suliyanto; Alfin Hikmaturokhman; Nurul Latifasari (Indonesian Journal of Food Technology, 2026)
Background: Nutmeg (Myristica fragrans Houtt.) is one of Indonesia’s leading spice commodities and is widely cultivated in the eastern regions of the country as well as several areas in southern Java. The quality of nutmeg seeds plays a crucial role in determining the quality of the oil produced; therefore, evaluating the characteristics of local nutmeg in comparison with industrial standards is essential. Purpose: This study aimed to compare the characteristics of local nutmeg seeds and oil with industrial standards based on physical and chemical parameters. Method: Industrial-standard nutmeg seeds of low, medium, and high quality were obtained from Piru, Maluku, while local nutmeg seeds were collected from Majenang and Banjarpatroman. Nutmeg oil was extracted using a mechanical pressing method involving shell removal, seed crushing, heating at 50–55°C, and oil pressing. Analyses were conducted on moisture content, pH, color parameters (L*, a*, and b*), free fatty acid (FFA) content, and acid value. Result: The results showed that local Banyumas nutmeg seeds had a higher moisture content than industrial-standard nutmeg seeds. In addition, local nutmeg oil exhibited higher FFA content and acid value, indicating lower oil quality. The color characteristics of local nutmeg seeds and oil also showed greater variation than those of the standard samples, reflecting differences in postharvest handling and processing practices. Overall, the physical and chemical characteristics of local nutmeg seeds and oil differed from industrial standards. Therefore, improved management practices, ranging from cultivation and postharvest handling to processing, are required to produce nutmeg oil that meets industrial quality standards.